Sucrose synthase gene family in common bean during pod filling subjected to moisture restriction - Morales-Elias, Norma Cecilia; Martínez-Barajas, Eleazar; Bernal-Gracida, Lilia Angélica; Vázquez-Sánchez, Monserrat; Galván-Escobedo, Iris Grisel; Rodriguez-Zavala, Jose Salud; López-Herrera, Amelia; Peña-Valdivia, Cecilia Beatriz; García-Esteva, Antonio; Cruz-Cruz, Carlos Alberto; González-Arnao, María Teresa; Jiménez-Galindo, José Cruz; et al. (Frontiers in Plant Science, 2024)
In common bean (Phaseolus vulgaris L.), leaf photosynthesis is significantly reduced under drought conditions. Previous studies have shown that some drought-tolerant cultivars use the pod walls to compensate the decreased photosynthesis rate in leaves by acting as temporary reservoirs of carbohydrates to support seed filling. Here, we describe a comprehensive molecular characterization of Sucrose synthase (SUS, EC 2.4.1.13) gene family through a genome-wide analysis and evaluated the effects of terminal drought on reproductive structures, specifically the pod walls. Seven PvSUS genes were located on six different chromosomes and had 8-16 intron-exon structures (8-16 exons). The PvSUS protein sequences revealed conserved catalytic domains, with molecular weights ranging from 90.5 to 105.1 kDa and lengths from 799 to 929 amino acids. Phylogenetic analysis grouped these sequences into three main clusters with seven subgroups, indicating divergence from SUS sequences in other plant species. Using a docking sequence, we predicted three-dimensional (3-D) structures and evaluated the active sites. Bioinformatics analysis of promoter regions suggested that PvSUS genes may respond to light, hormone signaling, and stress stimuli. Greenhouse experiments were conducted using the cv. OTI, identified as having intermediate drought tolerance. Plants at the R8 growth stage were maintained with regular irrigation at 100 % field capacity (FC) or with water restriction to maintain 50 % of field capacity. Pods were harvested 5, 10, 15, and 20 days after anthesis. An increase in PvSUS activity under water restriction was associated with higher levels of fructose, while sucrose concentration also increased. qRT-PCR analysis revealed that PvSUS1, PvSUS3, and PvSUS4 were strongly expressed during seed development under water restriction. The fluorescent sucrose analog esculin indicated that transport across the plasma membrane might contribute to the increase in the pith cell diameter of pedicels. The results provide a systematic overview of the PvSUS gene family in P. vulgaris, offering a framework for further research and the potential functional application of PvSUS genes.